Design and realization of a two axis system designated for mini solar tower - Reski, Khelifi; Gama, Amor; Belaid, Abd Elfateh; Yettou, Fatiha; Bezza, Bedraddine; Belroul, Rafika; Mostefaoui, Mohammed (University of Eloued جامعة الوادي, 2018)
In this work, we present a design of a mathematical model used in the simulation of the behavior of a two-axis solar tracking system (heliostats). This system is used as part of a project of a mini solar tower installed in the region of Ghardaïa. Then we start with the mechanical design of heliostats using SolidWorks software. After that, we went ahead with the realization of this system.
International Symposium on Mechatronics and Renewable Energies El-Oued 10- 11 December 2018
Keywords: solar tracking, solar tower, heliostats, SolidWorks